Design, construction and signal processing of an accelerograph for the CISMID accelerograph network - del Carpio Salinas, Jorge Alberto (2006)
Our location in the world makes us a country with a high seismic risk. Taking into account that the information produced during a seismic event is of vital importance for the study carried out by seismology, it is necessary to use the appropriate type of instrumentation to record these data. Currently, electronics provides the necessary technology for the study of phenomena of this type. The design and construction of a Digital Accelerograph will allow us to carry out a detailed study of a seismic movement and the effect caused on the structure of buildings. Finally, we can say that the construction of an instrument of this type at a low cost will allow repowering and increasing the CISMID accelerographic network and, in general, improve the knowledge of seismic phenomena at the national level.